High Water Mark Determination Based on the Principle of Spatial Continuity of the Swash Probability - Liu, Xin; Xia, Jianhong (Cecilia); Blenkinsopp, C.; Arnold, L.; Wright, Graeme (Coastal Education and Research Foundation, 2014)
This study presents a model that determines the position of the high water mark (HWM) based on the spatial continuityof inundation probability due to swash for a range of HWM indicators. These indicators include mean high water (MHW),high water line (HWL), and a number of shoreline features, such as the vegetation line. HWM identifies the landwardextent of the ocean and is required for cadastral boundary definition, land-use and infrastructure development along theforeshore ,and for planning associated with climate change adaptation. In this paper, shoreline indicators are extractedusing an object-oriented image analysis (OOIA) approach. Ten-year hourly swash heights (shoreline excursion length)are fitted into a cumulative distribution function. The probability that swash will reach the various HWM indicators overa 10 y period is then estimated. The spatial continuity distances of the swash probability of HWM indicators arecalculated using semivariogram models that measure similarity of swash probability. The spatial continuity distance isdefined as the distance between the lower bound of sampling position (the most seaward HWM indicator) and theposition where autocorrelation, or the similarity of swash probability of the various HWM indictors, approaches zero. Thelatter is considered as the HWM position in this study. This HWM determination method is evaluated at two study sitesat different latitudes and with distinct coastal features.